Menelaah Konsep Emmanuel Levinas Tentang Home Sebagai Pusat Spasial dalam Proses Pemanusiaan: Examining Emmanuel Levinas' Concept of Home as a Spatial Center in The Humanization Process - Kosat, Oktovianus (Jurnal Filsafat Indonesia, 2024)
This article discusses the concept of home in the philosophical thought of Emmanuel Levinas. Levinas has a rich background in philosophical thought, especially in the field of ethics. The purpose of this article is to examine and analyze Levinas’ concept to gain an understanding of the home as an ethical space that encourages relationships and responsibility between people. The philosophical analysis in this article uses the literature study method and concentrates on Levinas’s concepts found in the book ’Totality and Infinity’. Levinas reveals that home is a spatial center that inspires the process of humanization because it is a place for humans to get answers to all their hopes. According to Levinas, home is a space that has a close relationship with human existence. Home is not only a place to live or a place for ordinary activities, but also a special space with philosophical and ethical meanings. Home is a representation of life; a place to start and sustain life; a place to enjoy life; a place to determine the true existence of human beings. Levinas’ concept allows humans to work and shape everything they have in order to give birth to hospitality, openness to accept the ’Other’ in every encounter with the world outside their home. Levinas emphasizes that the concept of home forms the basis of ethical interaction that encourages the development of true humanity. Through in-depth analysis of the concept of home, it is found that home is not only a material object or physical place, but also refers to the process of forming ethical awareness of each individual in building relationships and responsibilities towards fellow humans and the environment. This concept can be used as a reference to understand humans and their ownership, and can be studied and examined in various contexts.